Silent struggles: Unveiling the unspoken epidemic of domestic violence against infertile women in Egypt - Elsayeda Hamdy Nasr Abdelhalim; Ateya Megahed Ibrahim; Hanan Elzeblawy Hassan; Nadia Mohamed Wahba; Samah Alsaid Ahmed Moawd (Elsevier, 2024)
Background: Globally, the issue of domestic violence (DV) against women remains a paramount concern in public health. However, a distinct facet of this challenge revolves around DV targeting women grappling with infertility, presenting a unique nexus with their overall well-being. This study endeavors to unravel the prevalence, associated determinants, and diverse manifestations of domestic violence against infertile women. Methods: The investigation unfolded within the Center for the Diagnosis and Treatment of Delayed Reproduction and the Gynecological Outpatient Clinic at Beni-Suef University spanning from the first of March to the end of July 2022. Employing a cross-sectional descriptive approach, the study engaged 200 infertile women actively seeking infertility treatment. Data acquisition transpired through an interview questionnaire tailored for the purpose. Results: Among surveyed women, 69.0 % reported experiencing physical violence due to infertility, while 65.5 % reported verbal violence. Additionally, 36.5 % reported incidents of sexual violence, and 47.0 % reported being subjected to financial violence. Statistical analyses revealed noteworthy correlations between physical and verbal violence and various factors, including age (p = 0.013), types of infertility (p = 0.001), gender of children (p = 0.006, p < 0.0001), and frequency of coitus (p = 0.019, p = 0.012), respectively. Conclusion and recommendations: Domestic violence exerts a profound impact on the general well-being of women, particularly affecting their emotional and social dimensions. This study underscores a heightened prevalence of violence among infertile women, with verbal abuse emerging as the predominant form. Recognizing the pivotal role of domestic violence in women's health, it becomes imperative for healthcare professionals to proactively identify at-risk individuals. Tailored interventions, such as comprehensive training programs encompassing communication skills and problem-solving approaches, should be devised and implemented. Moreover, counseling sessions should involve both spouses, elucidating the detrimental effects and challenges associated with all forms of violence.